Peran mediasi job satisfaction pada pengaruh tunjangan dan kepemimpinan terhadap kinerja pegawai - Fitriyawati, Anita (Implementasi Manajemen & Kewirausahaan, 2022)
This study aims to analyze the effect of benefits and leadership on job satisfaction and employee performance and the role of job satisfaction mediation in the two relationships. This study used quantitative methods to test the models and hypotheses stated in the test. The sample used was the State Civil Apparatus (ASN) in Situbondo Regency, with a total sample of 175 respondents. The findings of this study state that benefits and leadership have a positive and significant effect on job satisfaction and employee performance. Then, in this study, job satisfaction could mediate the influence of benefits and leadership on employee performance. In addition, we also examined the discussion in depth in this study.